Analisis Perancangan Sistem Informasi Administrasi Program Studi Pendidikan Teknologi Informasi dan Komunikasi - Sulistiyarini, Dewi; Sabirin, Febrianto (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2018)
This study aims to determine the description of needs, data flow design, database design, and design of information systems administration interfaces PSTIK study program. The research used descriptive method with research form that is survey research. Research subjects are staff, leadership of study program and 60 students of study program. Data analysis technique is to describe the data collected. The results show that the administrative information system consists of seminars and theses, lecturer journals, incoming and outgoing letters, and reports that are tailored to functional requirements, interface needs, and performance needs. The flow of information system data consists of two entities ie students and staff. Students have 6 inflows and outflows, while staff has 10 inflows and outflows. The information system database consists of 16 entities with 8 interrelated relations. The information system interface is divided into two pages. The student page consists of 6 pages, while the staff page consists of three pages.